Precursor concentration dependent hydrothermal NiO nanopetals: Tuning morphology for efficient applications. (January 2019) - Pathak, Devesh K.; Chaudhary, Anjali; Mishra, Suryakant; Yogi, Priyanka; Saxena, Shailendra K.; Sagdeo, P.R.; Kumar, Rajesh
Abstract: A precursor's concentration dependent surface morphologies of NiO nanopetals (NPs) have been studied for designing application-specific nanomaterials by hydrothermal technique. The surface morphologies, obtained using scanning electron microscopy, have been analysed using ImageJ to extract information about the dependence of petal thickness, petal density and linear porosity on the concentration at a given deposition and annealing temperatures. A detailed analysis shows how the synthesis parameters can be optimized to get a desired application specific nanostructure by taking an example of field emission properties. NiO NPs were prepared with three different precursor's concentrations out of which the sample prepared with lowest concentration was identified to show very good field emission property with high enhancement factor. Graphical abstract: Image 1 Highlights: NiO Nanopetals' density and thickness can be tailored by choosing appropriate concentration of precursors. Linear porosity and overall packing of nanopetals is a direct consequence of precursor concentration. Product of petal thickness and petal density gives a measure of the field emission quality.